Eksplorasi Potensi dan Proyeksi Retribusi Pelayanan Pasar: Studi Kasus Pasar Kranggan Yogyakarta - Sari, Rahma Fitriana; Ruti, Amanda; Sabila, Robith Ma'rufi; Bening, Banyu; Siregar, Hilda Octavana (Universitas 17 Agustus 1945 Jakarta, 2025)
Traditional markets play a vital role in the local economy. Not only serving as a distribution center for goods, but also as a source of Local Revenue (PAD) through retribution. With 29 market units spread across the city of Yogyakarta, this sector significantly contributes to the Local Revenue of the city of Yogyaka rta through retribution. However, the estimation of retribution revenue is often inaccurate, hindering the establishment of realistic targets. Therefore, the purpose of this research is to explore the potential and project the revenue from market levy at Pasar Kranggan Yogyakarta on a micro level based on the number of stand units and tariffs, as well as to project macro revenue for the period 2025 to 2030 using the Least Square calculation model. Our study’s results reveal the potential revenue of Pasar Kranggan in 2025 amounting to Rp808,616,160. The macro revenue projection using the Least Square method shows a consistent upward trend with the assumption of ceteris paribus. This research is expected to provide a tangible contribution in supporting the management policy of PAD in Yogyakarta City.